Peran Unilever Dalam Pemulihan Ekonomi Indonesia Pasca Pandemi - Muhammad Difo Hanggarjita; Arie Kusuma Paksi (Jayapangus Press, 2022)
Unilever is one of the largest multinational companies/MNCs in Indonesia. Unilever was formed with the noble goal of wanting to build a human life that has a view and purpose in life in order to create a prosperous and good life to live. This study aims to find out what efforts or contributions Unilever has made to Indonesia regarding Indonesia's economic recovery after the pandemic. In this study using qualitative methods and from the data collected, it can be concluded that Unilever is a company engaged in various fields of life that always tries to do its best to help prepare all needs for a prosperous life. Unilever's goal is to try to provide positive things also to regions or countries that are part of Unilever's business operations, such as providing assistance to the state and also providing counseling to the community. Unilever's contribution efforts to the country and its people are a mandatory part of a company, namely the Corporate Social Responsibility/CSR program. In accordance with Indonesian government regulations where every company must have CSR as its responsibility to the surrounding environment and maintain good relations with the community.